Rights Not Rescue - Zeffiro, Andrea; Lofaro, Nadia (My University, 2024)
A zine documenting four international workers' rights days.
A zine project researched, created, and published by Critical Data Studio in consultation with the Sex Workers' Action Program Hamilton.
Keywords: zine; labour rights